Local Historiography Study of Datuk Ahim's Baju Rajah: The Symbolic Meaning and Social Values of the Jambi Malay Community - Yoan Mareta; Anny Wahyuni (UIN Imam Bonjol Padang, 2025)
Jambi is one of the regions in Indonesia with a unique collection of local historiographies, one of which is the Baju Rajah a clothes that blends the cultural traditions of the Jambi Malay people with the spiritual beliefs of the community during the struggle for independence. This clothes belongs to Ibrahim Abdul Gani, a Red Sash Commander from Parit Deli, Kuala Tungkal, who contributed to defending Indonesia’s independence from 1948 to 1949. It is believed that the Baju Rajah possesses protective powers through the Rajah inscriptions and prayers embroidered on its fabric, making it a spiritual shield against enemy attacks, particularly from Dutch troops. This study aims to analyse the symbolic meaning of the Baju Rajah as a cultural artifact, the context of the Jambi Malay community’s beliefs regarding the power of Rajah, and the role of this artifact in strengthening local identity and narratives of struggle. The method used in this study is a qualitative paradigm through descriptive analysis to explore the relationship between the historical value of the Baju Rajah and its symbolic and social meanings within the Jambi Malay community. The results of the study indicate that, within a historical context, the Baju Rajah functions as a symbol of courage and collective protection. Meanwhile, the social values that can be identified reveal that the Baju Rajah is not merely a sacred text to be recited, but also a cultural artifact that can be seen, touched, and integrated into the spiritual identity of the Jambi Malay community.